2007
DOI: 10.1080/13651820701646222
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation in a hepatic porcine model: correlation of CT and histopathologic findings

Abstract: Microwave ablation with a novel device results in consistently sized and shaped lesions. Importantly, we did not observe any significant heat-sink effect using this device, a major difference from RFA techniques. This system offers a viable alternative for creating fast, large ablation volumes for treatment in liver cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 27 publications
6
47
1
Order By: Relevance
“…The CT appearance of regions of MV ablation revealed areas of hypodensity and lack of perfusion that did not enhance after the injection of medium contrast, similar to that seen with other methods of thermal ablation (19)(20)(21). The tissue vaporization was shown as air density (21).…”
Section: Comparison With Radiological Findingsmentioning
confidence: 73%
See 4 more Smart Citations
“…The CT appearance of regions of MV ablation revealed areas of hypodensity and lack of perfusion that did not enhance after the injection of medium contrast, similar to that seen with other methods of thermal ablation (19)(20)(21). The tissue vaporization was shown as air density (21).…”
Section: Comparison With Radiological Findingsmentioning
confidence: 73%
“…Investigations on the influence of vascular occlusion on the lesion size confirmed that this manoeuvre increased the ablated area (8,9,13,19), more in peripheral lesions than in those adjacent to major vessels (19). Interestingly, the effects of the blood flow interruption were greater when it was the portal vein rather than the hepatic artery (probably due to the greater flow of the former and the increased heat-sink effect), and even greater when both these vessels were occluded simultaneously (Pringle manoeuvre) (8,9).…”
Section: Macroscopic Anatomymentioning
confidence: 92%
See 3 more Smart Citations